Reliability and validity assessment of the Turkish version of the emotional availability and responsiveness in intrapartum care scale (ear-ic) - Yıldırım Varışoǧlu, Yeliz; Irmak Vural, Pınar (My University, 2024)
Background: Emotional availability and responsiveness in intrapartum care increase women's birth satisfaction, comfort, and quality of nursing/midwifery care. In Turkey, there is no instrument for measuring emotional availability and responsiveness in intrapartum care. Aim: An established translation, reliability, and validation approach was used to obtain the Turkish form of the A-EAR-IC scale. Methods: A descriptive cross-sectional study was used. This study was conducted in Istanbul, Turkey. The study sample consisted of 132 Turkish midwives working in the birth room. The construct validity of the scale was tested using confirmatory factor analysis, whereas the concurrent scale validity was tested using the Emotional Labor Behavior Scale. Internal consistency analysis was performed to test the reliability of the scale. Results: The results of the EAR-IC measure showed that it fit the one-factor model. The goodness-of-fit indices of the one-factor model containing eight items were acceptable. The instrument showed satisfactory content validity (I-CVI =0.80-1.00, S-CVI =0.88). According to CFA, the structure with one factor showed acceptable model fit ( χ2/df: 1.74, CFI: 0.96, IFI: 0.96, RMSEA: 0.07, and SRMR: 0.02). Concurrent validity of the instrument was assessed with the "in-depth behavior"subscale of the Emotional Labor Behavior Scale for Nursing. Spearman's correlations revealed that the EAR-IC was moderately positively correlated with the in-depth behavior concern subscale of the ELBS (rho =0.62, P < 0.001). Conclusion: The Turkish version of the EAR-IC is a suitable, effective, and reliable instrument for measuring the emotional aspects of intrapartum caregiving midwives.
Keywords: Emotional Adjustment; Empathy; Midwifery; Obstetric Nursing; Reliability and Validity